Comparative Policy Analysis of Early Childhood Curriculum Frameworks: Adapting Australian EYLF Values to Strengthen Indonesia’s Kurikulum Merdeka - Novita Ashari; Rachma Hasibuan; Mallevi Agustin Ningrum1 (Universitas Sulawesi Barat, 2026)
While early childhood education (ECE) globally aims to nurture holistic child development, the structural and philosophical execution varies significantly across nations. This study establishes a comparative policy analysis between two prominent frameworks: the Australian Early Years Learning Framework (EYLF) and Indonesia’s Kurikulum Merdeka. Utilizing a qualitative document analysis approach, this research examines the core philosophies, operational structures, and implementation challenges of both curricula. The analysis reveals that while the EYLF anchors its pedagogy heavily on sociocultural interactions, intentional play, and institutionalized family partnerships, Kurikulum Merdeka drives its focus toward curricular autonomy, contextual flexibility, and the civic-moral dimensions of the Pancasila Student Profile. Despite these divergent cultural and systemic origins, the findings indicate a profound synergy in their shared commitment to child-centered and reflective learning environments. Rather than advocating for a literal adoption, this study offers critical policy recommendations for adapting the universal benchmarks of the EYLF—particularly its robust quality assurance and formative assessment methods—to fortify pedagogical bottlenecks currently faced in the nationwide rollout of Kurikulum Merdeka within Indonesian ECE centers.